The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/jf204862d
|View full text |Cite
|
Sign up to set email alerts
|

Xanthigen Suppresses Preadipocyte Differentiation and Adipogenesis through Down-regulation of PPARγ and C/EBPs and Modulation of SIRT-1, AMPK, and FoxO Pathways

Abstract: Xanthigen is a source of punicic acid and fucoxanthin derived from pomegranate seed and brown seaweed, respectively with recognized triacylglycerol-lowering effects in humans, yet the mechanism remains to be fully elucidated. The present study investigated the inhibitory effects of Xanthigen, fucoxanthin, and punicic acid (70% in pomegranate seed oil) on the differentiation of 3T3-L1 preadipocytes. Xanthigen potently and dose-dependently suppressed accumulation of lipid droplets in adipocytes compared to its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 47 publications
1
74
0
Order By: Relevance
“…The high efficiency of xanthigen in improving the lipid metabolism was shown in both experimental and clinical studies. In the in vitro study on 3T3-L1 preadipocytes, xanthigen suppressed the adipocyte differentiation and accumulation of lipid droplets more efficiently than its components, FX and pomegranate seed oil [43]. Further analysis revealed that among key events which could mediate these effects are downregulation of peroxisome proliferator-activated receptor γ (PPARγ), CCAAT/enhancer binding proteins (C/EBP) β and δ, and fatty acid synthase, with concomitant upregulation of AMP-activated protein kinase signaling pathways [43].…”
Section: Combination Of Fx With Oilsmentioning
confidence: 94%
“…The high efficiency of xanthigen in improving the lipid metabolism was shown in both experimental and clinical studies. In the in vitro study on 3T3-L1 preadipocytes, xanthigen suppressed the adipocyte differentiation and accumulation of lipid droplets more efficiently than its components, FX and pomegranate seed oil [43]. Further analysis revealed that among key events which could mediate these effects are downregulation of peroxisome proliferator-activated receptor γ (PPARγ), CCAAT/enhancer binding proteins (C/EBP) β and δ, and fatty acid synthase, with concomitant upregulation of AMP-activated protein kinase signaling pathways [43].…”
Section: Combination Of Fx With Oilsmentioning
confidence: 94%
“…Lai et al (2012) investigated the effects of fucoxanthin combined with pomegranate seed oil standardized for punicic acid in a compound formula (Xanthigen®). The combination of these two supplements suppressed accumulation of lipid droplets in adipocytes, downregulated PPARγ, cytosine‐cytosine‐adenosine‐adenosine‐thymidine (CCAAT)/enhancer binding protein, and fatty acid synthase.…”
Section: Examples Of Natural Thermogenic Agentsmentioning
confidence: 99%
“…Fucoxanthin is converted to fucoxanthinol and amarouciaxanthin-A. This metabolite of fucoxanthin in white adipose tissue suppresses adipocyte differentiation and development (Yim et al, 2011;Lai et al, 2012) investigated the inhibitory effects of fucoxanthin, on the differentiation of preadipocytes and recognized as triacylglycerol-lowering agent in humans which is also observed by (Hu et al, 2012).…”
Section: Anti-obesity Activitymentioning
confidence: 89%